Improving the Charge Injection in Organic Transistors by Covalently Linked Graphene Oxide/Metal Electrodes. (11th February 2016) - Chen, Xiaosong; Zhang, Suna; Wu, Kunjie; Xu, Zeyang; Li, Hongwei; Meng, Yancheng; Ma, Xueming; Liu, Liwei; Li, Liqiang
Abstract : Electrodes, one of the key components of organic field‐effect transistors (OFETs), exert great influence on the device performance as well as circuit fabrication. Conventional metal electrodes generally show poor contact quality with organic semiconductors, especially in bottom‐contact geometry. Development of appropriate modification materials and methods for metal electrodes is an efficient way to improve OFET performance, which is, however, quite a challenging task. In this work, a facile strategy is developed to modify the metal surface with graphene oxide (GO) via covalent bonds for application in OFETs, which has not been reported before. This selective covalent modification strategy is compatible with diverse patterning techniques, and the covalently linked GO‐Au electrode exhibits strong robustness against solvent treatment. Remarkably, the GO‐Au electrode shows very good generality with both p‐type and n‐type organic semiconductors, which contributes to the realization of p‐/n‐type OFETs with significantly improved performance compared with the pristine Au electrode. The facile and low temperature modification method, compatibility with diverse patterning techniques, robustness against solvent treatment, good generality with organic semiconductors, and high OFET performance enable the strategy to be very promising for application in the field of organic electronics. Abstract : Covalent modification of Au electrodes with graphene oxide (GO) is demonstrated for application in organic field‐effect transistors (OFETs). Such a modification strategy possesses merits such as low processing temperature, compatibility with patterning techniques, robustness against solvent treatment, and generality with both p‐/n‐type organic semiconductors. OFETs with improved performance are constructed with the covalently linked GO‐Au electrode.